PERSPEKTIF TINGKAT TRANSPARANSI DAN AKUNTABILITAS DANA DESENTRALISASI KE DAERAH DAN ANGGARAN DANA DESA - Melisa Yanuar Susilo; Ishak Ishak; Hasanuddin Hasanuddin; Sudirman Sudirman; Ahmad Ahmad (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
The results of this research are based on Law Number: 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments regulating the new design of transfer funds to regions, regional income and expenditure. Likewise, it regulates how to monitor and provide evaluation of regional spending so that any existing budget can be used effectively and efficiently. The Ministry of Finance continues to strive to solve and eliminate gaps in the misuse of transfer funds to regions and village funds while seeking harmony between central and regional fiscal policies. This research aims to evaluate the level of transparency and accountability of transfers to regional and village funds through cash account management and assess the quality of government cash management and also evaluate government account management in increasing government revenue. This research uses a qualitative descriptive method by utilizing secondary primary data originating from various literature. From 2022 to 2023, it is even estimated that by the end of 2024, transfer funds deposited in regional government accounts throughout Indonesia at regional banks will average more than IDR 100 trillion. Deposition of funds will disrupt development and public service activities. In fact, it is hoped that government spending will be realized, which is the main stimulus for regional economic movements. By joining regional governments in the Treasury Single Account (TSA), all aspects of financial resource mobilization and expenditure can be managed as a whole by the government for the benefit of the people. Apart from strengthening and responding to the challenges of limited government financial resources. Existing idle cash can generate income. The participation of the Regional Government in implementing the Treasury Single Account (TSA) does not reduce the autonomy that has been mandated.